Salazar’s propaganda in English: an insight into the role of translation in Atlantic alliances - Chumbo, Isabel (2017)
This paper will focus on the translation of Salazar’s speeches into English as a tool to disseminate a good image about Portugal. Translation commissioned from within the Estado Novo (1930-74) regime is an emerging topic in the 20th century translation history, since archives have only recently unveiled this aspect. Initially the work will analyse how the regime commissioned and controlled this kind of textual production in several languages, thus showing evidence of the role of translation in the production and circulation of a specific type of political thought. The speeches were chosen according to the target culture where they were to be published. Some light will be shed on the criteria behind these publications. Then, more attention will be paid to the translation of the dictator’s speeches into English, which were compiled in one volume under the title Doctrine and Action, published in 1939, by Faber&Faber in London. The translations took over a year to be published with several problems being risen throughout the process by the translator, the editor and even the author. Parallel texts found in archives will show the role of each of these agents in the process. A comparative analysis of the speeches is then carried out with the aim of understanding which changes occurred paying special attention to omissions. These silences in Salazar’s speeches in English are analysed through their omitted contents and categorized. These will be cross-examined with archival information which provide evidence of official intervention in certain aspects of the translation process, namely through letters written by the publisher T. S. Eliot, the representative at the Portuguese embassy in London and the Head of the Propaganda Office in Portugal. The main conclusion of this study is that several relevant translation strategies contribute to a difference between source and target texts, with a clear ideological intention towards a British target audience.